2017
DOI: 10.3389/fmicb.2016.02125
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gut Microbiome Dynamics in Developing Pekin Ducks and Impact of Management System

Abstract: Little to no research has been conducted on the gut microbiome of the Pekin duck, yet over 24.5 million ducks are raised for human consumption each year in the United States alone. Knowledge of the microbiome could lead to an understanding of the effects of growing conditions such as the use of prebiotics, probiotics, and enzymes in feeding practices, the use of antibiotics, and the sources of pathogenic bacteria in diseased ducks. In order to characterize changes in the caecal microbiome that occur as ducks d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 66 publications
6
51
0
1
Order By: Relevance
“…The decrease in Firmicutes (order Clostridiales ) associated with the increase in Bacteroidetes (order Bacteroidiales ) and Proteobacteria has already been highlighted in a previous study in the lab [ 30 ]. Furthermore, in Pekin ducks, the most abundant bacteria (more than 95%) over the first 36 days were also Firmicutes, in particular, the Clostridiales order, as in our study [ 29 ]. Interestingly, in our work, at Eof point, a strong increase in the abundance of Lactobacillus, as described in geese and ducks, was observed but not linked to the supplementation of probiotics [ 8 - 10 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The decrease in Firmicutes (order Clostridiales ) associated with the increase in Bacteroidetes (order Bacteroidiales ) and Proteobacteria has already been highlighted in a previous study in the lab [ 30 ]. Furthermore, in Pekin ducks, the most abundant bacteria (more than 95%) over the first 36 days were also Firmicutes, in particular, the Clostridiales order, as in our study [ 29 ]. Interestingly, in our work, at Eof point, a strong increase in the abundance of Lactobacillus, as described in geese and ducks, was observed but not linked to the supplementation of probiotics [ 8 - 10 ].…”
Section: Discussionsupporting
confidence: 72%
“…The rapid evolution of the diversity of intestinal microbiota during the early stages of development demonstrated by Best et al . [ 29 ] and Rey et al . [ 30 ] in ducks and the strong effect of strain inoculation in newborn chickens on the composition of microbiota [ 31 , 32 ] suggest that supplementation in ducklings will be more efficient in modulating microbiota and host physiology immediately after hatching.…”
Section: Introductionmentioning
confidence: 99%
“…The early consequences directly involve infant gut function and immune system, and they are even associated with the signatures of the late gut microbiota as well as health and fitness of a host. These findings, therefore, give rise to great interest in gut microbiota of ontogenetic development in vertebrates such as birds, broilers, pig, and fish (Jami et al, 2013 ; Waite et al, 2014 ; Bakke et al, 2015 ; Corrigan et al, 2015 ; Niu et al, 2015 ; Best et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more studies focus on the gut microbes, which play an important role in our lives. Previous studies have demonstrated that diets 3 , 4 , breeding patterns, ages, and feed additives can impact the poultry gut microbes with respect to diversity, composition, and community structure 5 , 6 . Firmicutes, Bacteroidetes and Proteobacteria are the dominant phyla in poultry gut lumen.…”
Section: Introductionmentioning
confidence: 99%